Konstruksi Daya Tarik Seksual Wanita (Analisis Wacana Terhadap Teks Berita Mengenai Daya Tarik Seksual Pada Wanita Dalam Situs Vemale Rubrik Relationship Periode 2013) - FIRDASARI, Luthfi; , Nur Latifah Umi Satiti, MA; , Rinasari Kusuma, M.Ikom (2015)
The background of this research are: The media often show a women who only focuses on the appearance of the ideal female body, beautiful face, slender body, slender legs, and white skin. Mass media more emphasis on certain beauty standards which it has penetrated the mind of women and of course very difficult to avoid. The appearance of a woman's body that is so striking in the mass media as if it could give the impression that the most important thing for women is a pretty face and physical ideal to be able to lure and attract the opposite sex. Being a women means to be beautiful. Women who are not physically beautiful is not attractive. That's what's shaping the perception of women and make it difficult for a women like her body. The purpose of this research is: To find out how the construction of female sexual attractiveness on the site rubric Vemale Relationship period in 2013 based on the idea of women journalists. The method used in this research is descriptive and qualitative and methods of data collection techniques by collecting news and articles contained in the rubric Relationship of January to December 2013 and then performed the data analysis. Analysis of the data used is the model Sara Mills discourse analysis to examine and assess the position of the subject, the object, the writer and the reader. From the results of this research note that Vemale through women journalist as narrator (the subject) constructs the sexual attractions was not always associated only with the physical appearance of the ideal that says that a women attractions if it has an ideal body shape is slim, beautiful face, do not have excess fat in part- parts of the body, flat stomach, toned breasts, curvy hips and a plump rump. Women sexual activity shown in the rubric Relationship Vemale site is through how to walk, how to talk, how to look, how to behave and how to wear clothes that show the women sexuality as well as the ability to attract the opposite sex. Through the female journalists, especially women readers become aware of misunderstanding that had been believed.